Rare presentation of mucopolysaccharidosis with neuro-leptospirosis - M., Thulasi; P. M., Suresh; Pon Jeba, Merceline Alice; Samuel, Steeve Gnana (International Journal of Contemporary Pediatrics, 2022)
In this case report, we present a 10-year-old boy who was a known case of Hunters disease who presented with complaints of fever, vomiting, altered sensorium for 2 days. On examination he was febrile and had moderate hepatosplenomegaly. Lab investigation showed anaemia with thrombocytopenia and fever workup turned positive for leptospirosis. In view of altered sensorium, MRI brain was done which revealed a large subdural hematoma with midline shift which required parietal craniectomy with evacuation. From this case study, we reported that in a patient with underlying lysosomal storage disorder, vasculitis secondary to endothelial damage by leptospirosis along with thrombocytopenia can cause severe intracranial bleeding even with higher platelet counts.